2013
DOI: 10.1186/1741-7007-11-90
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of a protein-coding gene on B chromosomes of the Siberian roe deer (Capreolus pygargus)

Abstract: BackgroundMost eukaryotic species represent stable karyotypes with a particular diploid number. B chromosomes are additional to standard karyotypes and may vary in size, number and morphology even between cells of the same individual. For many years it was generally believed that B chromosomes found in some plant, animal and fungi species lacked active genes. Recently, molecular cytogenetic studies showed the presence of additional copies of protein-coding genes on B chromosomes. However, the transcriptional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 42 publications
(46 reference statements)
1
50
0
Order By: Relevance
“…In Drosophila albomicans, an actively transcribed unit of the B-chromosome was identified, which showed sequence homology with the subcentromeric region of both the ancient X and neo-X chromosomes (Zhou et al 2012). In the Siberian roe deer, Capreolus pygargus, three A-chromosome-located genes were found on the B-chromosome, one of which was transcribed in fibroblast culture (Trifonov et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila albomicans, an actively transcribed unit of the B-chromosome was identified, which showed sequence homology with the subcentromeric region of both the ancient X and neo-X chromosomes (Zhou et al 2012). In the Siberian roe deer, Capreolus pygargus, three A-chromosome-located genes were found on the B-chromosome, one of which was transcribed in fibroblast culture (Trifonov et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some protein-coding genes have also been identified on the B chromosomes of certain species (Miao et al, 1991;Lamatsch et al, 2011;Yoshida et al, 2011;Martis et al, 2012). Some of these are thought to have functional significance for their host (Miao et al, 1991;Yoshida et al, 2011) and exhibit transcriptional activity (Trifonov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Carchilan et al (2009) showed, in rye, the presence of B-specific transcribed DNA sequences belonging to highcopy families with similarity to mobile elements, and Zhou et al (2012) have characterized a B chromosome-linked scaffold that contains an actively transcribed unit. Recently, it has been shown the transcription of a protein-coding gene on B chromosomes of the Siberian roe deer (Capreolus pygargus) (Trifonov et al 2013) and Banaei-Moghaddam Abstract The genetic inertness of supernumerary (B) chromosomes has recently been called into question after finding several cases of gene activity on them. The grasshopper Eyprepocnemis plorans harbors B chromosomes containing large amounts of ribosomal DNA (rDNA) units, some of which are eventually active, but the amount of rRNA transcripts contributed by B chromosomes, compared to those of the standard (A) chromosomes, is unknown.…”
Section: Introductionmentioning
confidence: 99%